Construction of smart older adults care service model driven by primary health care - Zhang, Lechuan; Xu, Xiaoyan (Frontiers in Public Health, 2023)
With the advent of all-round population aging in recent years, how to provide for the elderly has become the focus of government departments and society. The conventional senior service model cannot meet the needs of today’s elderly service, which has many problems such as backward information platform construction, low quality of elderly service and “digital divide”. To solve the existing problems, this paper used grassroots medical and health drive to establish a smart senior care service model. Through the experiment, it can be found that the intelligent senior care service mode has absolute advantages in nursing data recognition compared with the conventional senior care service mode. The identification accuracy of all kinds of daily nursing data of the smart senior care service model was above 94%, while that of the conventional senior care service model was below 90%. The smart senior care service model could improve the quality of senior care services, which helped realize the diversified service mechanism for the elderly and better cultivate senior care professionals. Therefore, it is meaningful to study the smart senior care service model by using the grassroots medical and health drive.